Arterial and end-tidal Carbon Dioxide Tension Changes during Spinal Anaesthesia in Upper Abdominal Laparoscopic Surgeries: A Comparison with General Anaesthesia - Masum, Abdullah; Alam, Md Rabiul; Haque, Mozibul; Yasmin, Rubina; Khan, Shah Newaz H (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Nowadays, laparoscopic surgeries are being performed under subarachnoid block (SAB) safely. Aims: This study was to compare the arterial and end-tidal carbon dioxide (CO2) tension changes during spinal and general anaesthesia (GA) in CO2 pneumoperitoneum for upper abdominal laparoscopic surgeries. Settings and Design: This was a prospective randomized comparative clinical study. Materials and Methods: Eighty patients posted for upper abdominal laparoscopic surgeries were randomly allocated to two groups either to receive standard GA or lumbar SAB. Results: The demographic profiles of both the groups were comparable. The PaCO2 was increased gradually and sustained at its peaks within 20±4.37 minutes in both the groups. The mean±SD revealed to be higher in Group B (41.5500±2.1315) than Group A (40.8460±2.1136), but the difference between the two was not statistically significant (P=0.6142). There was a gradual increase in ETCO2 over the initial 10±2.07 minutes and reached a plateau within 20±5.74 minutes in both the groups and declined faster after deflation of pneumoperitoneum in SAB group. The mean±SD was found to be higher in Group B (33.923±1.642) than Group A (33.408±1.772), but it was also not statistically significant (P=0.4492). The difference of the arterial blood pH between the groups was not statistically significant. Three (7.5%) patients developed transient urinary retention and 2 (5%) patients suffered from post-dural puncture headache in SAB group. Conclusions: Arterial and end-tidal CO2 tension changes during upper abdominal laparoscopic surgery under SAB remain within physiological limit and comparable to the CO2 tensions under GA. However, per-operative complications in SAB are greater, while it is lesser in postoperative period in comparison to GA. SAB may be adopted in ASA physical status I patients with proper preoperative counselling. J Bangladesh Coll Phys Surg 2019; 37(1): 13-18